Pengaruh Self Monitoring Terhadap Perilaku Agresi - Wiwin Pratiwi Nurdam (Jurnal Pendidikan Dasar dan Menengah (Dikdasmen), 2025)
This study aimed to determine the effect of self-monitoring on the aggressive behavior of class XI students at SMA Negeri 8 Luwu Utara. The independent variable was self monitoring. The dependent variable was aggressive behavior. This study applied quantitative research methods with additional validity and realibility tests. The sampling technique was probality sampling technique with the type of stratified ramdom sampling method. Respondents in this study were students of class XI SMA Negeri 8 North Luwu namely 55 people. The tool used to manage the data in this study was using the SPSS type 22 application. The results of this study show that the effect of self-monitoring on the aggressive behavior of students at SMA Negeri 8 Luwu Utara is 12.7% but not significant (0,05).